2008
DOI: 10.1038/ajh.2008.27
|View full text |Cite
|
Sign up to set email alerts
|

Cardioprotective Mechanism of Telmisartan via PPAR- -eNOS Pathway in Dahl Salt-Sensitive Hypertensive Rats

Abstract: These results suggest that the cardioprotective mechanism of telmisartan may be partly due to improvement of endothelial function associated with PPAR-gamma-eNOS, oxidative stress, and Rho-kinase pathway.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
70
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(77 citation statements)
references
References 22 publications
6
70
1
Order By: Relevance
“…33 Recently, it has been reported that telmisartan ameliorated cardiac remodeling in DSsensitive hypertensive rats through PPAR-g-endothelial nitric oxide synthase pathway. 34 Although Takano et al 35 reported that PPAR-g was expressed in neonatal normal cardiac myocytes, in this study, immunohistochemical results have shown that only marginal or trivial immunoreactivity for PPAR-g was detected in myocardium of normal rats. Interestingly, we also observed increased expression of PPAR-g in rats with DCM in line with the previous reports 29,36,37 and these changes were significantly decreased by telmisartan treatment ( Figures 1c, d, 2a and a1).…”
Section: Discussioncontrasting
confidence: 56%
“…33 Recently, it has been reported that telmisartan ameliorated cardiac remodeling in DSsensitive hypertensive rats through PPAR-g-endothelial nitric oxide synthase pathway. 34 Although Takano et al 35 reported that PPAR-g was expressed in neonatal normal cardiac myocytes, in this study, immunohistochemical results have shown that only marginal or trivial immunoreactivity for PPAR-g was detected in myocardium of normal rats. Interestingly, we also observed increased expression of PPAR-g in rats with DCM in line with the previous reports 29,36,37 and these changes were significantly decreased by telmisartan treatment ( Figures 1c, d, 2a and a1).…”
Section: Discussioncontrasting
confidence: 56%
“…Independent of AT1 receptor-blocking activity, telmisartan is responsible for the additional antioxidant and anti-inflammatory activities. The drug acts as a partial agonist of PPAR-g. 14,15,35,36 Activation of PPAR-g induces catalase gene expression and inhibits nuclear factor-kB, thus, combating oxidative stress and downregulating most of the proinflammatory responses. 37,38 Another possible mechanism is that telmisartan, by blocking AT1 receptor, allows Ang-II to interact more with the Ang-II type-2 receptor (AT 2 ) which, on the contrary, provides cellular protective action against oxidative stress and excitotoxic damage.…”
Section: Discussionmentioning
confidence: 99%
“…p38 MAPK and myosin phosphatase targeting subunit (MYPT-1) phosphorylation was measured as described in detail previously [20][21][22][23] .…”
Section: P38 Mapk and Mypt-1 Phosphorylationmentioning
confidence: 99%
“…Histological detection of superoxide anion in the LV was performed using dihydroethidium (DHE) as described previously 18,19,21,23) .…”
Section: Detection Of Superoxide Anion In the LVmentioning
confidence: 99%
See 1 more Smart Citation